2019
DOI: 10.3390/s20010082
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Clothing-Mounted Sensors with Wearable Sensors for Movement Analysis and Activity Classification

Abstract: Inertial sensors are a useful instrument for long term monitoring in healthcare. In many cases, inertial sensor devices can be worn as an accessory or integrated into smart textiles. In some situations, it may be beneficial to have data from multiple inertial sensors, rather than relying on a single worn sensor, since this may increase the accuracy of the analysis and better tolerate sensor errors. Integrating multiple sensors into clothing improves the feasibility and practicality of wearing multiple devices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Tables 1 and 2 summarize a review of recent works, sorted by year of publication, related to human activity recognition through wearables, while Figure 1 depicts some relevant conclusions. Overall, most of the studies detected a variable number of human activities, from one to nine, including the identification of sports [14][15][16], activities of daily living (ADL) [17][18][19], also featuring house activities [20] such as washing, shelving items, sweeping, ironing, vacuuming, driving, etc. In most studies, the typical attempted activities were: walking, jogging, standing, sitting, lying, squatting, going upstairs/downstairs, running, among others.…”
Section: Related Work 1human Movement Analysis (Hma)mentioning
confidence: 99%
“…Tables 1 and 2 summarize a review of recent works, sorted by year of publication, related to human activity recognition through wearables, while Figure 1 depicts some relevant conclusions. Overall, most of the studies detected a variable number of human activities, from one to nine, including the identification of sports [14][15][16], activities of daily living (ADL) [17][18][19], also featuring house activities [20] such as washing, shelving items, sweeping, ironing, vacuuming, driving, etc. In most studies, the typical attempted activities were: walking, jogging, standing, sitting, lying, squatting, going upstairs/downstairs, running, among others.…”
Section: Related Work 1human Movement Analysis (Hma)mentioning
confidence: 99%
“…It is also germane to consider that tag attachment stability may change over time in longer-term deployments. These issues have long been recognised in the wearable sensors industry for humans (Jayasinghe et al, 2019). Consequently, we cannot, in good faith, compare VeDBA or wingbeat amplitudes of tropicbirds between seasons although the wingbeat frequency will be unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Tabia et al [47] identified human activities such as running, jogging and running by using Naıve Bayes and Support Vector Machine (SVM) classifiers. Jayasinghe et al [22] conducted experiments using a combination of clothing mounted sensors and wearable sensors for movement analysis and activity classification with a focus on running, walking, sitting and riding in a bus. By calculating correlation coefficients for each sensor pair, they suggest that even though the two data streams have some notable differences, results indicate high classification accuracy.…”
Section: Activity Classificationmentioning
confidence: 99%